Two puzzles about appositives: Projection and perspective shift - Koev, Todor (Proceedings of Sinn und Bedeutung, 2019)
This paper solves two puzzles about the interpretation of appositive constructions in English: (i) it explains why appositives robustly PROJECT even though they are interpreted in situ with respect to order-dependent phenomena such as discourse anaphora; (ii) it analyzes certain non-projective readings of appositives as instances of PERSPECTIVE SHIFT, a phenomenon that bears striking similarities with the phenomenon of shifted indexical pronouns. To solve the first puzzle, I assume that appositives are interpreted in surface position but adopt a less standard mechanism of operator scope according to which operators can bind lexical predicates or other operators. Since appositives form ForcePs and Force operators cannot be bound, it follows that appositives project even when placed in the syntactic scope of a higher operator. With respect to the second puzzle, I argue that shifted appositives are evaluated with respect to a secondary speech context introduced by a verb of saying or inferred from the larger discourse. Since the two mechanisms of projection and perspective shift are independent, they can be given a uniform analysis.